Pengaruh NPM, PBV, DER, Harga Minyak dan Inflasi terhadap Harga Saham Industri Pertambangan pada LQ45 di Bursa Efek Indonesia Periode 2012 – 2016 - Richma Sri Achrani (Universitas Batanghari Jambi, 2019)
The aims of this study are to analyze the effect of Net Profit Margin (NPM), Price to Book Value (PBV), Debt to Equity Ratio (DER), Oil Price and Inflation on Stock Prices. This study was taken because there are still differences between the research study with each other and there is a difference between the real state of research study with each other and there is a difference between the real of research data with existing theory. The analytical method used in this study is multiple regression analysis performed with SPSS 19. The object of this research is Mining Industry registered in LQ45 Bursa Efek Indonesia period 2012-2016. The Mining Industry consists of three companies, that is PT Adaro Energy Tbk., PT Aneka Tambang Tbk., and PT Vale Indonesia Tbk. The results showed that the variables Net Profit Margin (NPM), Price to Book Value (PBV), Debt to Equity Ratio (DER), Oil Price and Inflation significantly influence the price of stocks simultaneously on the LQ45 Mining Industry in Bursa Efek Indonesia period 2012-2015. From result of research that is PBV and DER variable partially have a significant effect to Stock Price at Mining Industry LQ45 at Bursa Efek Indonesia, NPM, Oil Price and Inflation partially no significant effect on Stock Price at Mining Industry LQ45 in Bursa Efek Indonesia period 2012 - 2016.